Review of the Experimental Methods for Evaluation of Windows’ Thermal Transmittance: From Standardized Tests to New Possibilities - Simões, Nuno (2023)
One of the most important parameters that indicate the energy performance of a window system is the thermal transmittance (U-value). Many research studies that deal with numerical methods of determining a window’s U-value have been carried out. However, the possible assumptions and simplifications associated with numerical methods and simulation tools could increase the risk of under- or over-estimation of the U-value. For this reason, several experimental methods for investigating the U-value of windows have been developed to be used either alone or as a supplementary method for validation purposes. This review aims to analyze the main experimental methods for assessing the U-value of windows that have been published by national and international standards or as scientific papers. The analysis criteria include the type of the test in terms of boundary conditions (laboratory or in situ), the part of the window that was tested (only the center of glazing or the entire window), and the data analysis method (steady-state or dynamic). The experimental methods include the heat flow meter (HFM) method, guarded hot plate (GHP) method, hot box (HB) method, infrared thermography (IRT) method, and the so-called rapid U-value metering method. This review has been set out to give insights into the procedure, the necessary equipment units, the required length of time, the accuracy, the advantages and disadvantages, new possibilities, and the gaps associated with each method. In the end, it describes a set of challenges that are designed to provide more comprehensive, realistic, and reliable tests.